Long-term follow up of patients treated with a DNA vaccine (pTVG-hp) for PSA-recurrent prostate cancer - Tommaso P. Tonelli; Jens C. Eickhoff; Laura E. Johnson; Glenn Liu; Douglas G. McNeel (Taylor & Francis Group, 2024)
We have previously reported two single-agent phase I trials, evaluating the dose or schedule, of a DNA vaccine (pTVG-HP) encoding prostatic acid phosphatase (PAP) administered with GM-CSF as the adjuvant. These were in patients with PSA-recurrent, radiographically non-metastatic, prostate cancer (PCa). We report here the long-term safety and overall survival of these patients. Specifically, 22 patients with non-metastatic, castration-sensitive PCa (nmCSPC) were treated with pTVG-HP, 100-1500 µg, administered over 12 weeks and followed for 15 y. 17 patients with non-metastatic castration-resistant PCa (nmCRPC) were treated with 100 µg pTVG-HP with different schedules of administration over 1 y and followed for 5 y. No adverse events were detected in long-term follow-up from either trial that were deemed possibly related to vaccination. Patients with nmCSPC had a median overall survival of 12.3 y, with 5/22 (23%) alive at 15 y. 8/22 (36%) died due to prostate cancer with a median survival of 11.0 y, and 9/22 (41%) died of other causes. Patients with nmCRPC had a median overall survival of 4.5 y, with 8/17 (47%) alive at 5 y. The presence of T-cells specific for the PAP target antigen was detectable in 6/10 (60%) individuals with nmCSPC, and 3/5 (60%) individuals with nmCRPC, many years after immunization. The detection of immune responses to the vaccine target years after immunization suggests durable immunity can be elicited in patients using a DNA vaccine encoding a tumor-associated antigen.Trial Registration: NCT00582140 and NCT00849121